Biutiful: En los márgenes de la la cosmópolis neoliberal (Periphērica, 2022)
In Alejandro González Iñárritu’s Biutiful, the city operates as a sort of anti-model exposing the dark side of neoliberal economies in larger fashionable cities, with an emphasis in precarization and exclusion and dynamics of violence against migrant populations. To this end, he uses an aesthetics of incongruence and a focus over a motley society, in permanent tension and negotiation between variegated groups. These strategies coexist with two other themes: exclusion represented as a form of expulsion or excrecence, and the appeal to memory as an ethical imperative that disrupts the logic of monetary calculus in which the main characters live immersed.